CEO inside debt holdings and trade credit. (23rd December 2021) - Hasan, Mostafa Monzur; Hossain, Ashrafee T.; Hossain, Takdir
Abstract: This study investigates the relationship between chief executive officer (CEO) inside debt holdings (pension benefits and deferred compensation) and use of supplier‐provided trade credit. We provide evidence that CEO inside debt holdings are negatively related to the use of trade credit. Our results are robust to the use of alternative regression estimation and alternative measures of key variables. We exploit the final enforcement of Section 409A of the Internal Revenue Code (IRC) as an exogenous shock to inside debt holdings. Our difference‐in‐difference regression analysis establishes a causal relationship. In addition, we provide evidence that our documented results are not driven by omitted variable bias. We also employ instrumental variable regression estimation using heteroskedasticity‐based instruments to mitigate the endogeneity concern. Our cross‐sectional analyses reveal that the relationship between CEO inside debt holdings and trade credit is more pronounced in firms with poor information environments and greater financing constraints. Overall, findings from our study suggest that CEO inside debt has important implications for the financing policy of the firm.